ASSOCIATION BETWEEN A HEALTH PSYCHOLOGY COURSE AND HEALTH-PROMOTING BEHAVIOUR AMONG MALAYSIAN UNDERGRADUATE PSYCHOLOGY STUDENTS: A QUASI-EXPERIMENTAL STUDY - Zailanudin, Aira Misha; Subramaniam, Gopal; Mohamed, Nor Firdous (JIP (Jurnal Intervensi Psikologi), 2026)
ABSTRACT: Health-promoting behaviours play an important role in enhancing students’ overall well-being and quality of life; however, maintaining consistent healthy lifestyle practices can be challenging during university years. This study examined the impact of a 14-week Health Psychology course on health-promoting behaviours among undergraduate psychology students (N = 54).  A prospective one-group pretest–posttest quasi-experimental design was utilized, with data collection measured using the Health-Promoting Lifestyle Profile II (HPLP-II). Results revealed significant post-course improvements in overall health-promoting behaviours (t = 3.346, p = .002). At the subscale level, significant improvements were observed in physical activity (t = 2.005, p = .05), health responsibility (t = 2.766, p = .008), and interpersonal relationships (t = 2.605, p = .012). These findings suggest that participation in a structured Health Psychology course may be associated with improvements in selected domains of health-promoting behaviours among undergraduate students. However, due to the absence of a control group, results should be interpreted cautiously. Future studies should utilize controlled or randomized designs to better evaluate the effectiveness of health psychology courses in promoting sustained behavioural change. Keywords: health psychology, health-promoting behaviour, undergraduate university students, quasi-experimental design ABSTRAK: Perilaku hidup sehat memainkan peran penting dalam meningkatkan kesejahteraan dan kualitas hidup mahasiswa; namun, mempertahankan gaya hidup sehat secara konsisten dapat menjadi tantangan tersendiri selama masa perkuliahan. Penelitian ini bertujuan untuk mengkaji pengaruh mata kuliah Psikologi Kesehatan selama 14 minggu terhadap perilaku promosi kesehatan di kalangan mahasiswa sarjana psikologi (N = 54).  Desain kuasi-eksperimen prospective one-group pretest–posttest digunakan dalam penelitian ini, dengan pengumpulan data yang diukur menggunakan instrumen Health-Promoting Lifestyle Profile II (HPLP-II). Hasil penelitian menunjukkan adanya peningkatan signifikan pada keseluruhan perilaku promosi kesehatan setelah mengikuti mata kuliah tersebut (t = 3.346, p = .002). Pada tingkat subskala, peningkatan signifikan ditemukan pada aktivitas fisik (t = 2.005, p = .05), tanggung jawab kesehatan (t = 2.766, p = .008), dan hubungan interpersonal (t = 2.605, p = .012). Temuan ini menunjukkan bahwa partisipasi dalam mata kuliah Psikologi Kesehatan yang terstruktur berkaitan dengan peningkatan pada domain tertentu dari perilaku promosi kesehatan di kalangan mahasiswa. Namun, karena tidak adanya kelompok kontrol, hasil penelitian ini harus diinterpretasikan dengan hati-hati. Penelitian selanjutnya disarankan menggunakan desain terkontrol atau acak (randomized) untuk mengevaluasi lebih lanjut efektivitas mata kuliah psikologi kesehatan dalam mendorong perubahan perilaku yang berkelanjutan. Kata kunci: psikologi kesehatan, perilaku hidup sehat, mahasiswa sarjana muda, kuasi-eksperimen